Some integral inequalities involving the k-Beta function and generalized convex stochastic processes. - Hernández H, Jorge Eliecer (Revista MATUA, 2019)
In the present work some integral inequalities that involve the k-Beta function and stochastic processes whose absolute values posses the property of convexity, or P-convexity, s-convexity in the second sense or (m; h1; h2)-convexity are established. Similarly, some others integral inequalities for stochastic processes whose r-th powers of its absolute values posses these kind of generalized convexity are established making use of the Hölder’s inequality and power mean inequality.